Combining morphological and metric variations in the study of design and functionality in stone weights. A comparative approach from continental and insular Patagonia, Argentina - Cardillo, Marcelo (2015)
This paper aims to apply statistical and comparative methods to characterize and establish the potential functionality of artifacts with little or, virtually, no modification, such as lithic weights which are used as a part of fishing lines or nets. To this end, two samples fromcontrasting archeological and environmental contexts of the Patagonian and Tierra del Fuego coasts are used. Contour analysis (Fourier outlines) and Multiple Factorial Analysis were used to compare different data sets and to assess variation ranges. The results suggest that it is possibleto determine differential shape and size ranges. With this information it is then possible to assign these artifacts to different environmental contexts and/or types of fishing gears.